Big Water The Making of the Borderlands Between Brazil, Argentina, and Paraguay - Frank, Zephyr; Freitas, Frederico; Blanc, Jacob (University of Arizona Press, 2018)
Big Water explores four centuries of the overlapping histories of Brazil, Argentina, and Paraguay (the Triple Frontier), and the colonies that preceded them. Examining an important area that includes some of the first national parks established in Latin America and one of the world's largest hydroelectric dams, this transnational approach illustrates how these three nation-states have interacted over time. From the Jesuit reductions in the seventeenth century to the flows of capital and goods accelerated by contemporary trade agreements, the Triple Frontier region has proven fundamental to the development of Brazil, Argentina, and Paraguay, as well as to the Southern Cone and South America itself. Although historians from each of these three countries have tended to construct narratives that stop at their respective borders, the contributors call for a reinterpretation that goes beyond the material and conceptual boundaries of the Triple Frontier. In offering a transnational approach, Big Water helps transcend nation-centered blind spots and approach new understandings of how space and society have developed throughout Latin America. These essays complicate traditional frontier histories and balance the excessive weight previously given to empires, nations, and territorial expansion. Overcoming stagnant comparisons between national cases, the research explores regional identity beyond border and geopolitical divides. Thus, Big Water focuses on the uniquely overlapping character of the Triple Frontier and emphasizes a perspective usually left at the periphery of national histories.